Efficient crystal structure materials as reactive sorbent for the CO2 and CH4 adsorption and storage - R. Essehli (1837924) (2024)
The efficient dirubidium cobalt bis(dihydrogendiphosphate) dihydrate compound is successfully synthesized in a solution and used as a reactive sorbent for the CO2 and CH4 gases adsorption and storage. A crystal of this Rb2Co(H2P2O7)2·2H2O compound has been isolated and characterized by single X-ray diffraction analysis and was found to crystallize in the triclinic system (P1¯) with the cell parameters (Å): 6.980(1), 7.370(1), 7.816(1), 81.74(1), 70.35(1), 86.34(1); V = 374.68(9) Å3, Z = 2. The crystal-packing consists of a three-dimensional framework made upon corners and edges sharing of [RbO7], [H2P2O7] and [CoO6] entities, furthermore linked by a network of H-bonds. The UV–Vis spectroscopy revealed usual transitions between the ground state 4T1g and the upper levels 4T2g, 4A2g and 4T1g (P). Moreover, the CO2 and CH4 gases sorption measurements were successfully performed at two different temperatures (25 and 45 °C) and various pressures ranging from vacuum to 50 bar. Our results show that rate of CO2 and CH4 capturing was 3.10 mmol/g and 2.35 mmol/g at temperature 25 °C and pressure 50 bar, respectively. This compound showed a clear potential for CO2/CH4 adsorption and storage thereby paving the way towards its exploration and adaptation for capturing and collecting carbon dioxide and greenhouse gases from the air, and their conversion into hydrocarbon fuels using existing mature technologies. We have also conducted density functional theory calculations to study the CO2 and CH4 adsorption properties of Rb2Co(H2P2O7)2·2H2O. The simulation results show enhanced adsorption of both types of molecules on the surface of the material. Other Information Published in: Scientific Reports License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1038/s41598-024-57060-8